Preventing physician burnout: satisfaction or something more? - Stuart Slavin (BMC, 2019)
Abstract Physician burnout and depression have been recognized as serious international problems and the secondary costs of poor physician mental health are substantial. Interventions to address this problem can be split into two categories: those focusing on the individual, and those addressing the work environment. Individual-focused programs often include instruction in mindfulness, nutrition, and exercise, while those in the work environment have focused largely on stressors such as administrative burden, electronic health records, and productivity pressures. The recent IJHPR article entitled "Burnout and intentions to quit the practice among community pediatricians: Associations with specific professional activities", by Grosman et al., offers an additional path to address burnout and well-being in pediatricians through increasing of hours in more satisfying professional activities. While "satisfaction" was the metric in this study, what lay at the root of that satisfaction may be deeper and more profound. What the study does not measure is that the less-burned out physicians who felt greater satisfaction may have also felt a greater sense of meaning in their lives. Grossman et al. rightly urge health care managers to encourage diversification of the pediatrician's job by enabling greater engagement in the identified 'anti- burnout' professional activities, however more can and should be done. Physicians themselves should take an active role in both the seeking of, and connection to, meaning. Burnout and frustration, understandably, may have led some doctors to possess a sense of cynicism that has obscured meaning in their lives. If physicians cannot find a path to meaning on their own, they should seek colleague partners, coaches, or therapists to assist. Physicians can advocate for programs to reduce work-force stressors, but they can also advocate for formal programs such as Healers Arts programs, Schwartz rounds, and narrative medicine programs to help reconnect to meaning in their daily clinical work. Brief courses in cognitive behavioral techniques may also help in combating problematic mindsets endemic in medicine such as negativity bias, maladaptive perfectionism, and pessimistic explanatory style. With effort, a growth mindset, and when needed, guidance and some reinforcement, these negative and toxic mindsets can diminish; they can fade, and further open physicians to the healing power of meaning.